Usability Study of Integrated RULA-KinectTM System for Work Posture Assessment - Halim, Isa; Radin Umar, Radin Zaid; Ahmad, Nadiah; Jamli, Mohamad Ridzuan; Syed Mohamed, Muhammad Syafiq; Moataz Albawab, Tarek Mhd; Lim Abdullah, Muhammad Haziq; Padmanathan, Vinothini (International Journal of Integrated Engineering, 2018)
A good work posture is one of vital contributors to occupational health and to increase the efficiency of industrial workers. Recently, numerous research works have developed an Integrated RULA- KinectTM system for work posture assessment; however, usability of the developed system remains unknown. The objective of this study was to develop a prototype of Integrated RULA-KinectTM system. Additionally, this study performed usability testing on the Integrated RULA- KinectTM system and RULA Employee Assessment Worksheet to determine feedbacks and reactions from the potential users. A focus group session was conducted among eight potential users, which divided into 2 groups (novice and expert). The results of the focus group session revealed that both novice and expert users agreed that the Integrated RULA-KinectTM system is easy to use compared to RULA Employee Assessment Worksheet. This study concluded that the Integrated RULA-KinectTM system is able to counter some limitations of the RULA Employee Assessment Worksheet.